2018
DOI: 10.1002/dev.21627
|View full text |Cite
|
Sign up to set email alerts
|

Low hair cortisol concentration and emerging attention‐deficit/hyperactivity symptoms in preschool age

Abstract: Previous research demonstrated hypoactivity of the HPA axis in children with attention-deficit/hyperactivity disorder (ADHD) or externalizing symptoms. We analyzed the predictive association between the long-term HPA axis activity and increasing symptoms of ADHD in the preschool period. The sample consisted of n = 125 4-year-old children and their families (including n = 64 children with elevated ADHD symptoms). ADHD symptoms were assessed by a structured clinical interview with the mother and by parent- and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Of the 28 studies included in this systematic review (see Table S1), 11 (39.3%) 21–31 were rated as having a high risk of bias, and 17 were rated as having a low risk of bias. For the 11 studies with a high risk of bias, the rating was due to potential confounding: Researchers failed to adjust potential confounders when examining the relationship between HCC and anthropometric factors.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 28 studies included in this systematic review (see Table S1), 11 (39.3%) 21–31 were rated as having a high risk of bias, and 17 were rated as having a low risk of bias. For the 11 studies with a high risk of bias, the rating was due to potential confounding: Researchers failed to adjust potential confounders when examining the relationship between HCC and anthropometric factors.…”
Section: Resultsmentioning
confidence: 99%
“…For the 11 studies with a high risk of bias, the rating was due to potential confounding: Researchers failed to adjust potential confounders when examining the relationship between HCC and anthropometric factors. Two studies also had potential bias in participant selection, as participants were recruited conveniently from a previous trial 22 or selection was based on a prior defined distribution 26 . Three studies either included self‐reported height and weight data or did not clearly describe if height and weight were subjectively reported or objectively measured 22,26,32 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations